Critical skills of entry level animators in the contemporary South African computer animation industry - Makwela, Mashaole Jacob (My University, 2012)
This study investigates the views and opinions of computer animation practitioners about the critical skills required for entry level animators in computer-generated or digital animation design in South Africa. The literature review chapters of the study clarify the terms animation and creativity, examine the changes taking place in the animation discipline, and discuss the relative roles of technical and creative skills in computer animation productions, primarily based on Amabile’s componential model of creativity. The chapters that deal with the fieldwork describe the sequential mixed-methods design which was followed in this study to gather data in two phases, namely a survey with questionnaires (n = 16), and interviews (n = 7) at thirteen South African companies, six in Johannesburg and seven in Cape Town. The main aim of the first phase was to determine (a) which skills are considered more important for entry level animators, (b) whether technical skills or creative skills are considered more important in the selection process for new animators, and (c) whether institutions teaching computer animation should focus on technical skills or creative skills. The main aim of the second phase was to augment the questionnaire results with more detailed explanations. The results of the first phase indicate that according to the respondents computer animation education should focus primarily on creative skills. The results of the second phase confirm that creative skills are regarded as more important, and also elaborate on a number of factors, including job level, the nature of the company, and company size, which the respondents considered important during the first phase of data collection. The information gathered in the course of this study can be used directly by entry level practitioners, experienced animators and design students. The results can also guide the development of the South African animation industry and the revision of multimedia curricula.
M. Tech. (Multimedia, Department of Visual Arts and Design), Vaal University of Technology
Keywords: Computer animation; Digital animation; 776.70968; Computer animation.; Animators -- South Africa.